A feasibility study into the possibility of ionospheric propagation of low VHF (30-35 MHZ) signals between South Africa and Central Africa - Coetzee, Petrus Johannes (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2009)
The role of the South African National Defence Force (SANDF) has changed considerably in the last decade. The emphasis has moved from protecting the country's borders to peacekeeping duties in Central Africa and even further North. Communications between the peacekeeping missions and the military bases back in South Africa is vital to ensure the success of these missions. Currently use is made of satellite as well as High Frequency (HF) communications. There are drawbacks associated with these technologies (high cost and low data rates/interference respectively). Successful long distance ionospheric propagation in the low Very High Frequency (VHF) range will complement the existing infrastructure and enhance the success rate of these missions. This thesis presents a feasibility study to determine under what ionospheric conditions such low VHF communications will be possible. The International Reference Ionosphere (IRI) was used to generate ionospheric data for the reflection point(s) of the signal. The peak height of the ionospheric F2 layer (hmF2) was used to calculate the required antenna elevation angle. Once the elevation angle is known it is possible to calculate the required F2 layer critical frequency (foF2). The required foF2 value was calculated by assuming a Maximum Useable Frequency (MUF) of 20% higher than the planned operational frequency. It was determined that single hop propagation is possible during the daytime if the smoothed sunspot number (SSN) exceeds 15. The most challenging requirement for successful single hop propagation is the need of an antenna height of 23 m. For rapid deployment and semi-mobile operations within a jungle environment it may prove to be a formidable obstacle.
Keywords: Communications, Military -- South Africa; Communications, Military -- Africa, Central; Digital communications -- South Africa; Digital communications -- Africa, Central; Signals and signaling -- South Africa; Signals and signaling -- Africa, Central; Artificial satellites in telecommunication -- South Africa; Artificial satellites in telecommunication -- Africa, Central; Shortwave radio